Frontiers in Medicinal Chemistry - Atta-ur-Rahman. (Bentham Science Publisher, 2012)
Frontiers in Medicinal Chemistry is a book series devoted to the review of areas of important topical interest to medicinal chemists and others in allied disciplines. Frontiers in Medicinal Chemistry covers all the areas of medicinal chemistry, including developments in rational drug design, bioorganic chemistry, high-throughput screening, combinatorial chemistry, compound diversity measurements, drug absorption, drug distribution, metabolism, new and emerging drug targets, natural products, pharmacogenomics, chemoinformatics, and structure-activity relationships. Medicinal chemistry as a discipline is rapidly maturing. The study of how structure and function are related is absolutely essential to understanding the molecular basis of life. Frontiers in Medicinal Chemistry aims to contribute in a major way to the growth of scientific knowledge and insight, and facilitate the discovery and development of new therapeutic agents to treat debilitating human disorders. This book series is essential for any medicinal chemist who wishes to be kept informed and up-to-date with the latest and the most important advances.